A participação do setor privado na gestão da educação básica pública em municípios mineiros - Glecenir Vaz Teixeira (2017)
This research has investigated the private sector participations (Legal Private Foundations and Non-governmental Educational Organizations) at the Public basic educational Brazilian-system in five municipality of Minas Gerais. The aim of this work was to gather information on how these Foundations and Organizations have participated in the chosen cities as well analyzing the articulation which have taken local management. By revising their literature, it has found out, where upon their participation has been growing in the latest years, as well, the assembling of conveyance that give them a variety means. There are three identifying discursive manners for attaining towards the private sectors and logic orientation from public and private play-role action management, associated to the ideal of New Public Management. There were two hypotheses guiding this study. The first hypothesis has considered that the private sector participation occurred by acquiring technical resources and/or financial and/or material. The second hypothesis would involve the transferring of public financial resources for patronizing the private sector developed activities. By having either one or the other hypothetic situations, might lead to indicate different form for educational marketing. Investigation procedures initiated for selecting the cases for studied. Vale Foundation and Social Itaú Foundation 'choices due to their participation at the movement Everyone for Education. This selection defined the five municipalities towards there search field execution. The analysis method involved the contented study from the public and private play-roles, besides, documentations related to the participation from these lected cities. This research has come to findings that evidenced the participation from technical assessment, as though for considering Brazilian Public school managements as well as by formulating proposal and implementing the continued program to prepare educational personal. Almeida (2016) confirmed the findings that the foundation participation connected to the private sector has happened for receiving financial support from non-governmental organizations named by the author as Operational Arms. This research found that the private sector happened from two manners: In the first place, educational municipal managers demand and articulate the private sector for acting during their management period; on the other hand, the role-plays search in active way for municipal managers to implement their programs. On this studied no evidence for direct transferring for financial resources from the private sector into the local educational administration research. However, the participation contributed in contrast to execute services and allowance for using their facilities at the studied cases. It has been reveled that municipalities policy-management autonomy may contribute for creating differentiated manner stowards educational marketing.